SAMPLE TASKS IN CHEMISTRY FOR MILITARY SPECIALTIES - M.Sh.Islamova (American Journals Publishing, 2023)
This article presents considerations on the methodology for improving the military competence of cadets of the higher military education system with the help of special exercises and tasks in chemistry lessons. The article provides examples of tasks suitable in the specialty for cadets of the military aviation direction.
Keywords: military competence, chemicals, aviation, military practical task